Communication technologies for vehicles : 5th International Workshop, Nets4Cars/Nets4Trains 2013, Villeneuve d'Ascq, France, May 14-15, 2013. Proceedings - Berbineau, Marion (Lecture Notes in Computer Science, 2013)
This book constitutes the joint refereed proceedings of the 5th International Workshop on Communication Technologies for Vehicles/Trains, Nets4Cars 2013 and Nets4Trains 2013, held in Vilnius, Lithuania, in May 2013. The 12 full papers of the road track and 5 full papers of the rail track presented together with 3 invited talks were carefully reviewed and selected from 24 submissions. They address topics such as intra-vehicle, inter-vehicle and vehicle to infrastructure communications (protocols and standards), mobility and traffic models (models, methodologies, and techniques), testing, and applications.